State and Local Sales Taxes and Business Activity in the United States - Nicholas Saxon; Mehmet S. Tosun; Jingjing Yang (Institute for the Study of Labor (IZA), 2015)
There has been an increasing reliance on sales taxation in both the states and counties in the United States. In this paper, we are examining the relationship between state and local sales taxation and business activity in the U.S. by utilizing county-level data for the period 2002-2011. We have found significant negative association between the state and county combined sales tax rate and annual payroll of businesses particularly in the manufacturing sector. There is also evidence of spatial dependence particularly in the payroll response of businesses within the contiguous region. While we found no significant relationship with employment, there is also statistically significant negative association with retail establishments and small establishments with less than 10 employees. It is possible that businesses respond to a sales tax rate increase first, or more directly, by reducing payroll rather than employment. While the economic significance of these results, however, is not found to be overwhelmingly strong, policymakers should still pay attention particularly to how manufacturing businesses respond to sales tax rate tax changes in the form of changes in payroll, and the responses from the small retail establishments.
Keywords: H25; H71; H73; J21; 330; state and county sales tax; business activity; payroll; employment; number and size of establishments; United States